Woman and Fatwa: an Analytical Study of MUI’s Fatwa on Women’s Health and Beauty - Hanna, Siti; Mukri Aji, Ahmad; Tholabi, Ahmad; Amin, Muhammad (AHKAM : Jurnal Ilmu Syariah, 2024)
This study examines the fatwas on women’s health and beauty issued by the Indonesian Ulema Council (MUI), explicitly investigating the influence of particular madhhab on these fatwas. This influence will be evaluated in MUI’s fatwas on women’s health and beauty, including fatwas on menstrual suppression pills, abortion, female circumcision, plastic surgery, and botox injections for beauty and care. The doctrinal approach of legal research is applied to analyze the use of Islamic legal sources and arguments. This study shows that although the majority of Indonesian Muslims follow the Shafi’i school, MUI does not solely adhere to the Shafi’i school in formulating its fatwas. Instead, MUI also employs approaches from other madhhab, such as Hanafi, Maliki, and Hanbali. As various MUI’s fatwas have provided broad guidelines for the community, fatwas on women significantly influence the legal basis for government policies.  Abstrak: Kajian ini mengkaji fatwa-fatwa kesehatan dan kecantikan perempuan yang dikeluarkan oleh Majelis Ulama Indonesia (MUI) serta  secara eksplisit menyelidiki pengaruh mazhab tertentu terhadap fatwa-fatwa tersebut. Fatwa MUI yang dikaji menyangkut tentang kesehatan dan kecantikan perempuan, termasuk fatwa tentang pil penekan menstruasi, aborsi, sunat perempuan, operasi plastik, dan suntik botox untuk kecantikan dan perawatan. Pendekatan penelitian hukum doktrinal diterapkan untuk menganalisis penggunaan sumber dan argumentasi hukum Islam. Kajian ini menunjukkan bahwa meskipun mayoritas umat Islam di Indonesia menganut mazhab Syafi’i, namun MUI tidak semata-mata menganut mazhab Syafi’i dalam merumuskan fatwa-fatwanya. Sebaliknya, MUI juga menggunakan pendekatan dari mazhab lain, seperti Hanafi, Maliki, dan Hanbali. Karena fatwa-fatwa MUI tersebut  memberikan pedoman yang luas bagi masyarakat, maka fatwa tentang perempuan sangat mempengaruhi dasar hukum kebijakan pemerintah.